Neural Circuit Mechanisms Encoding Motivational States in Drosophila - Lee, Sang Soo (Curr Opin Neurobiol, 2020)
Animals engage in motivated behaviors, such as feeding and mating behaviors, to ensure their own survival and the survival of their species. However, the neural circuits mediating the generation and persistence of these motivational drives remain poorly understood. Here we review recent studies on the circuit mechanisms underlying motivational states in Drosophila, with a focus on feeding, courtship, and aggression. These studies shed light on the molecular and cellular mechanisms by which key drive neurons receive relevant input signals, integrate information, and decide on a specific behavioral output. We also discuss conceptual models for integrating these circuit mechanisms, distinguishing between those for homeostatically- vs non-homeostatically-regulated motivated behaviors. We suggest that the ability to trigger persistence of a motivated behavior may be a feature of integrator or apex/command neurons.